Taking regulatory T-cell therapy one step further. Issue 5 (October 2018) - Sicard, Antoine; Boardman, Dominic A.; Levings, Megan K.
Abstract : Purpose of review: Adoptive cell therapy using CD4 + FOXP3 + regulatory T cells (Treg) has emerged as a promising therapeutic strategy to treat autoimmunity and alloimmunity. Preclinical studies suggest that the efficacy of Treg therapy can be improved by modifying the antigen specificity, stability and function of therapeutic Tregs. We review recent innovations that considerably enhance the possibilities of controlling these parameters. Recent findings: Antigen-specific Tregs can be generated by genetically modifying polyclonal Tregs to express designated T-cell receptors or single-chain chimeric antigen receptors. The benefits of this approach can be further extended by using novel strategies to fine-tune the antigen-specificity and affinity of Treg in vivo . CRISPR/Cas 9 technology now enables the modification of therapeutic Tregs so they are safer, more stable and long lived. The differentiation and homing properties of Tregs can also be modulated by gene editing or modifying ex-vivo stimulation conditions. Summary: A new wave of innovation has considerably increased the number of strategies that could be used to increase the therapeutic potential of Treg therapy. However, the increased complexity of these approaches may limit their wide accessibility. Third-party therapy with off-the-shelf Treg products could be a solution.